Paraconductivity of (Bi,Pb) 2Sr2Ca2Cu3-xGexOy (Journal of Science and Technology, 2016)
The paraconductivity of (Bi, Pb)7Sr2Ca 2Cu 3-x (0 < x < 0.3) superconducting system has been investigated' The paraconductivity above T was determined from the Anderson-Zou fit to the format-state resistivity. Using the Aslamazov-Larkin theory, the dimensionality of the materials was determined. The value of the critical exponent -1) obtained for all the samples indicates that the superconductivity of the system in which Ge replaces Cu is of two-dimensional nature. Thus, the substitution of Ge for Cu does not affect the homogeneity in the superconducting fluctuations in the Cu-0 planes. There is evidence that the a-b plane conductivity dominates, although the crystallites in the polycrystalline samples are randomly oriented